(untitled) - Kriz, Josef (Doprava a spoje, 2011)
The paper describes problems with implementation of Engine Data Management 800 system for Zlin aircraft M 337 and M137. The EDM 800 is using the latest microprocessor technology and will monitor up to twenty-four critical parameters in engine, four times a second. This paper is a part of project: Implementation of scientific research knowledge to the Air Transport - ITMS 26220220010, which is realized at University of Zilina.